Challenges Faced by the Media under the Fragile State: Analytical Study of the Iraqi Media Reality - SAMEIR DEHIRB, ADNAN (ALBAHITH ALALAMI, 2025)
This study aims at defining the concept of the fragile state, a term that came into existence in 2014, when the states that had internal Problems and external interventions were referred to as the failure states. However, the indicators for their designation and the criteria adopted are 12 indicators that address all aspects of the State’s duties vis-a-vis its citizens. The study examined the reasons that led to the continuation of Iraq within the fragile states, and the selection of the five years within the time limits of the study due to the factors that led to the decline of Iraq and falling back within the most fragile countries. The study dealt with the fragile state challenges to the media reality as a result of the change of its structure because of changing the form of political system alongside the political transformations.The researcher has used the descriptive and the functional approach in the study to achieve the goal of research and analysis of the media reality, which has lost many of its basic elements to the public. The research arrived at a number of findings that revealed the reasons behind the fragility of the state and the challenges that have been reflected in the media reality which suffers from the lack of legal legislations providing access to information that is the right way to reach the truth that is still absent from the citizen who lives in a troubled environment due to the retreat of the political will and the conflicts between those in control of authority, which was a major cause of the fragility of the state, and their repercussions on the media reality, whose contribution at this stage was consistent with the orientations and rhetoric of the funding agencies of those means .In other words, it became a reflection of a divided society which is already divided at the level of sectarianism, nationalism and religion. The researcher identified the factors that influenced the media and their role in this transitional period, which was characterized by vulnerability due to weak state and performance of its functions. This requires drawing up plans, enacting legal legislations in an attempt to reduce this fragility and counter its collapse.